P‐24: Novel Pixel Structure for Improving Transmittance of High Resolution LCD. Issue 1 (May 2016) - Kang, Gyutae; Jang, Hun; Yang, Joonyoung; Jun, Myungchul; Kang, Inbyeong
Abstract : We introduce the new pixel structure named 'Gate Space Share (GSS)'. The new structure consists of the two transistors together in order to reduce the area of the transistors. Reducing the space of the transistor is efficient to the transmittance of the LCDs especially for the high resolutions LCDs. We achieved 40% higher transmittance than the conventional structure of the 5.0 inch Full HD mobile display.